Estilos de gestión en la sala de ordeño y su relación con la calidad de leche en establos de Lima, Perú - Sandoval-Monzon, Rocio (2025)
The aim of this study was to identify management styles in milking parlours and evaluate their impact on milk quality in dairy farms in the province of Lima. The study was conducted in 30 dairy farms in the province of Lima and at the Faculty of Veterinary Medicine of the UNMSM for 10 months, involving lactating cows in free-stall pens. Data collection included visits, surveys to dairy farm managers and workers, and analysis of milk samples. A non-experimental cross-sectional study was conducted to determine the relationship between management style in the milking parlour and milk quality. Management style was assessed through surveys covering three dimensions: tasks, people, and milking practices. Milk quality was analysed in terms of composition, hygiene, and sanitation. Statistical analysis used the two-step clustering method and a general linear model. The results of the study identified three management styles in milking parlours: managerial, informal, and social. The management style, characterized by strict protocols and a professional environment, showed the best milk quality in terms of composition, hygiene and sanitation. The informal style, common in smaller farms, presented deficiencies in hygiene and sanitation quality, with high bacterial counts. The social style, focused on staff well-being, had good compositional quality, but faced problems with temperature and prevalence of mastitis. In conclusion, the managerial management style is the most effective in maintaining high milk quality, while the informal and social styles require improvements in milking practice control and hygiene.